2008
DOI: 10.1002/jbt.20229
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of SH‐SY5Y human neuroblastoma cells in the cell cycle following exposure to organophosphorus compounds

Abstract: The current study investigated the relationship of the cell cycle phase (as G(0)/G(1), S, and G(2)/M) and cytotoxicity (as sub-G(1) DNA) to determine whether alterations in cell replication were associated with organophosphate (OP) compound induced cytotoxicity. Results demonstrated that, overall, OP compound--induced cell cycle changes were variable and depended on the OP compound, exposure concentration, and temporal relationship to cytotoxicity. Noncytotoxic OP compound treatments substantially decreased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Cyclin A binds to S phase cyclin dependent kinase 2 (Cdk2) and is required for the cell to progress through the S phase . Our results are in agreement with previous reports which showed checkpoint activation by genotoxins like OPs results in either cell cycle arrest and repair of the damage, senescence, or apoptosis. , In addition, a recent report also showed that 4-HT treatment successfully attenuated the docosahexaenoic acid induced cell cycle arrest and apoptosis in human pulmonary artery smooth muscle cells …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Cyclin A binds to S phase cyclin dependent kinase 2 (Cdk2) and is required for the cell to progress through the S phase . Our results are in agreement with previous reports which showed checkpoint activation by genotoxins like OPs results in either cell cycle arrest and repair of the damage, senescence, or apoptosis. , In addition, a recent report also showed that 4-HT treatment successfully attenuated the docosahexaenoic acid induced cell cycle arrest and apoptosis in human pulmonary artery smooth muscle cells …”
Section: Resultssupporting
confidence: 92%
“…52 Our results are in agreement with previous reports which showed checkpoint activation by genotoxins like OPs results in either cell cycle arrest and repair of the damage, senescence, or apoptosis. 53,54 In addition, a recent report also showed that 4-HT treatment successfully attenuated the docosahexaenoic acid induced cell cycle arrest and apoptosis in human pulmonary artery smooth muscle cells. 55 Doherty et al have demonstrated that the incidence of micronuclei increases after exposure to trichlorfon in human lymphoblastoid cells, which suggests that OPs are potentially genotoxic.…”
Section: -Ht Pretreatment Attenuates the Dichlorvos Mediated Change mentioning
confidence: 97%
“…Cellular checkpoints are signaling pathways evolved in eukaryotes to maintain genomic integrity. Several reports have shown that checkpoint activation by genotoxins such as OPs results in cell cycle arrest and repair of the damage, senescence or apoptosis (Mattiuzzo et al,2006; Carlson and Ehrich,2008). It is reported that dichlorvos showed stronger apoptosis‐inducing ability than chlorpyrifos at lower doses in human natural killer (NK) cells (Li et al,2007).…”
mentioning
confidence: 99%
“…Besides its cytotoxic and esterase-inhibitor effects, CPF treatment can also act on neuronal and dopaminergic markers since it can cause a decrease in TH expression, in dopamine (DA) levels [62,85] and in TUBB3 expression [85] but does not affect glutamic acid decarboxylase 65-kilodalton isoform (GAD65) protein expression which is a marker of GABAergic signaling [62]. Parathion and paraoxon alter the cell cycle status and have effects on f-actin, that may be related to alterations on neurite extension and secretion of neurotransmitters [116,117].…”
Section: -Impact Of Ops On Other Features Associated With Neuropathymentioning
confidence: 99%